The impact of macroeconomic variables on stock return: a study of Kuala Lumpur composite index (KLCI) / Siti Salihah Sadikin - Sadikin, Siti Salihah (Faculty of Business Management, 2017)
This study attempts to examine the impact of macroeconomic variables on Kuala Lumpur Composite Index (KLCI). Stock market has been investigated as one of the factor that a ffects the economic growth in Malaysia. This is because a well formulated stock market index can be a sensitive barometer of short run political and economic development. Therefore, it is important to study the effect of macroeconomic variables on stock return. The aim of the study is to investigate the impact of macroeconomic variables such money supply, interest rate, exchange rate and inflation rate on the returns of Kuala Lumpur Composite Index (KLCI) that listed in Bursa Malaysia. Secondly, this study’s purpose is to know the intensity of macroeconomic variables on price index of company listed on Kuala Lumpur Stock Exchange. Macroeconomic variables in this study are interest rate (T-bills), money supply (M2) and inflation rate (CPI) and exchange rate. The findings reveal that among four independent variables, only two variables which are exchange rate and inflation rate are significant with dependent variable. Whereas, interest rate and money supply shows insignificant result with stock prices. In addition, exchange rate shows the negative relationship in the first month. However, inflation rate have a positive relationship in the current month and shows the negative relationship after the first month differencing. The prices of stock for KLCI are taken from the monthly period 2008 until 2015 which is 8 years by using Multiple Linear Regression method.